2018
DOI: 10.1016/j.resuscitation.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromonitor-guided titrated care on brain tissue hypoxia after opioid overdose cardiac arrest

Abstract: In this model of opioid overdose cardiac arrest, brain tissue hypoxia is common and treatable. Further work will elucidate best strategies and impact of titrated care on functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Delineating the significance of brain tissue hypoxia as a modifiable factor, as opposed to an expected epiphenomenon in the natural history of HIBI, is essential. In animal models, MAP augmentation using exogenous vasopressors has demonstrated improved PbtO2 in thalamic and cortical tissue, structures which are exquisitely susceptible to secondary injury (9,11). We also observed a relationship between MAP and PbtO2 in individual patients over time.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Delineating the significance of brain tissue hypoxia as a modifiable factor, as opposed to an expected epiphenomenon in the natural history of HIBI, is essential. In animal models, MAP augmentation using exogenous vasopressors has demonstrated improved PbtO2 in thalamic and cortical tissue, structures which are exquisitely susceptible to secondary injury (9,11). We also observed a relationship between MAP and PbtO2 in individual patients over time.…”
Section: Discussionsupporting
confidence: 58%
“…Observational studies demonstrate that perturbations in CDO2 from hypotension (6,7) and hypocapnia (8) after ROSC during no-reflow are associated with worse neurological outcome. Animal models have confirmed the no-reflow phenomenon (9) and demonstrate that increasing CDO2 with mean arterial pressure (MAP) augmentation results in improved thalamic and subcortical brain tissue oxygenation (PbtO2) (10,11). A recent systematic review suggests increased MAP is associated with improved neurologic outcome following cardiac arrest (12).…”
Section: Introductionmentioning
confidence: 95%
“…Hyperoxemia may exacerbate oxygen free radical-mediated damage in the brain and promote pulmonary inflammation [4,30]. In contrast, a recent porcine model of CA demonstrated a reduced incidence of low brain tissue oxygenation in swine treated with a FiO 2 of 1.0 and a 20-mmHg increase in mean arterial pressure (MAP) from baseline compared to those treated with a SpO2 target of 94-98% and a MAP target of > 65 mmHg [31]. This may help explain our finding of a lower mortality associated with hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited data are available on the relationship between PbtO 2 and neurologic injury after cardiac arrest [ 22 , 23 ], a number of studies have suggested that the depth and duration of low PbtO 2 values correlate with unfavorable outcomes in patients with severe traumatic brain injury [ 24 , 25 , 26 , 27 ]. Our findings, together with those of these studies [ 24 , 25 , 26 , 27 ], indicate a plausible link between PbtO 2 and neurologic outcome among the survivors of the epinephrine group in the PARAMEDIC2 trial.…”
Section: Discussionmentioning
confidence: 99%
“…The epinephrine-induced, persistent reduction of PbtO 2 in the present study, in contrast to the rapid reversal of epinephrine-induced reduction of PbtO 2 observed in the study by Ristagno et al [ 5 ], might be due to the prolonged duration before treatment of cardiac arrest in the present study. No studies, to the best of our knowledge, have evaluated the effects of the duration of untreated cardiac arrest on the epinephrine-induced reduction of PbtO 2 , but several experimental studies using a model with relatively prolonged duration of untreated cardiac arrest reported findings suggestive of sustained reduction in PbtO 2 after ROSC [ 9 , 23 ]. In a study in which rats underwent 9 min or 12 min of asphyxial cardiac arrest followed by CPR including epinephrine administration [ 9 ], cortical PbtO 2 was similar to baseline until 15 min after ROSC but was lower than baseline from 30 min to 120 min after ROSC.…”
Section: Discussionmentioning
confidence: 99%